2019
DOI: 10.1021/acs.jpclett.9b02947
|View full text |Cite
|
Sign up to set email alerts
|

High Coulombic Efficiency Na–O2 Batteries Enabled by a Bilayer Ionogel/Ionic Liquid

Abstract: Sodium–oxygen (Na–O2) cells are a promising high energy density storage technology with a theoretical specific energy of 1605 Wh kg–1. However, this technology faces certain challenges in order to achieve both a high practical energy density as well as long-term cycling capability. In this Letter, a superior Coulombic cyclic efficiency, close to 100%, has been demonstrated by the use of a bilayer electrolyte composed of an ionogel and an ionic liquid electrolyte, reported herein for the first time. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The larger diameter cathode is employed in these cells due to previous studies which showed enhanced performance for this configuration when employing an IL electrolyte. This cell feature underlines the origins of this study which focuses on the ORR-OER cathode due to its limiting performance when paired with the excellent Na metal cycling performance of several IL systems. , Before testing, all cells were flushed with pure oxygen (Ultrahigh purity oxygen grade >99.999% oxygen, <5 ppm moisture, and <3 ppm hydrocarbon gas, Supagas) and rested for 3 h at 60 °C. The cells were tested galvanostatically by using a Biologic VMP 300 multichannel potentiostat, operated between 1.6 and 3.6 V vs Na/Na + at a constant current density of 0.1 mA cm –2 and with a capacity limitation of 0.30 mAh cm –2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger diameter cathode is employed in these cells due to previous studies which showed enhanced performance for this configuration when employing an IL electrolyte. This cell feature underlines the origins of this study which focuses on the ORR-OER cathode due to its limiting performance when paired with the excellent Na metal cycling performance of several IL systems. , Before testing, all cells were flushed with pure oxygen (Ultrahigh purity oxygen grade >99.999% oxygen, <5 ppm moisture, and <3 ppm hydrocarbon gas, Supagas) and rested for 3 h at 60 °C. The cells were tested galvanostatically by using a Biologic VMP 300 multichannel potentiostat, operated between 1.6 and 3.6 V vs Na/Na + at a constant current density of 0.1 mA cm –2 and with a capacity limitation of 0.30 mAh cm –2 .…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanofiber matts (CNF) were fabricated by electrospinning, as previously described. 34 In brief, the precursor solution, 9 wt % polyacrylonitrile (PAN), was prepared in dimethylformamide (DMF), which was stirred to obtain a homogeneous, clear solution. The solution was then loaded into a 5.5 mL plastic syringe for electrospinning.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…propylene carbonate, PC); ethers (e.g. dimethoxyethane, DME); others such as dimethyl sulfoxide (DMSO) 7 or ionic liquids 9,10 . Among all, tetraethylene glycol dimethyl ether (TEGDME) is the most used liquid electrolyte due its low volatility, wide electrochemical window (beyond 4.5 V versus Li 0 /Li + ) good solubility of metal alkali salts and relatively low cost [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Aprotic liquid electrolyte cells, also called “nonaqueous,” are the most popular because of their highest theoretical capacity . Common aprotic solvents are organic carbonates (e.g., propylene carbonate), ethers (e.g., dimethoxyethane), and others such as dimethyl sulfoxide (DMSO) or ionic liquids. , Among all, tetraethylene glycol dimethyl ether (TEGDME) is the most used liquid electrolyte because of its low volatility, wide electrochemical window (beyond 4.5 V vs Li 0 /Li + ), good solubility of metal alkali salts, and relatively low cost. However, its liquid nature prompts some drawbacks related to safety issues such as the potential leaking of the toxic and flammable organic electrolyte in the cell …”
Section: Introductionmentioning
confidence: 99%